1992
DOI: 10.1007/bf01258278
|View full text |Cite
|
Sign up to set email alerts
|

The Shapley value for cooperative games under precedence constraints

Abstract: Cooperative games are considered where only those coalitions of players are feasible that respect a given precedence structure on the set of players. Strengthening the classical symmetry axiom, we obtain three axioms that give rise to a unique Shapley value in this model. The Shapley value is seen to reflect the expected marginal contribution of a player to a feasible random coalition, which allows us to evaluate the Shapley value nondeterministically. We show that every exact algorithm for the Shapley value r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
194
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 211 publications
(196 citation statements)
references
References 13 publications
2
194
0
Order By: Relevance
“…The properties ADD, EFF, NP and SQ degenerate to be the properties introduced by Owen [12] when we restrict the domain of CM CN in the setting of traditional games with a coalition structure. Furthermore, the property HST degenerates to be the property proposed by Faigle and Kern [23] …”
Section: Characterizations Of the Given Coalitional Valuementioning
confidence: 99%
“…The properties ADD, EFF, NP and SQ degenerate to be the properties introduced by Owen [12] when we restrict the domain of CM CN in the setting of traditional games with a coalition structure. Furthermore, the property HST degenerates to be the property proposed by Faigle and Kern [23] …”
Section: Characterizations Of the Given Coalitional Valuementioning
confidence: 99%
“…For games on distributive lattices, Faigle and Kern (1992) showed that the Shapley value is the unique operator…”
Section: The Weber Set and The Core In Simple Gamesmentioning
confidence: 99%
“…4 Other solution concepts in simple games Faigle and Kern (1992) introduced the hierarchical strength h S (i) in distributive lattices L as follows.…”
Section: The Weber Set and The Core In Simple Gamesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a more general model for cooperative games with or without transferable utilities (TU or NTU) is necessary in order to describe situations in which cooperation is restricted. In this paper we adopt the model of Faigle and Kern (1992) who assume that the set of players has a hierarchical structure generated by some partial order relation. Only those coalitions may form (are feasible) that satisfy the following condition: With any player all of her subordinates (i.e., the players preceding her according to the partial order relation) must also be members of the coalition.…”
Section: Introductionmentioning
confidence: 99%